Applying the Tailored Implementation in Chronic Diseases framework to inform implementation of the Preferences Elicited and Respected for Seriously Ill Veterans through enhanced decision-making program in the United States Veterans Health Administration - Haverhals, Leah M.; Magid, Kate H.; Kononowech, Jennifer (Frontiers in Health Services, 2022)
In 2017, the National Center for Ethics in Health Care for the United States Department of Veterans Affairs (VA) commenced national roll-out of the Life-Sustaining Treatment Decisions Initiative. This national VA initiative aimed to promote personalized, proactive, patient-driven care for seriously ill Veterans by documenting Veterans' goals and preferences for life-sustaining treatments in a durable electronic health record note template known as the life-sustaining treatment template. The Preferences Elicited and Respected for Seriously Ill Veterans through Enhanced Decision-Making (PERSIVED) quality improvement program was created to address the high variation in life-sustaining treatment template completion in VA Home Based Primary Care (HBPC) and Community Nursing Home programs. This manuscript describes the program that focuses on improving life sustaining treatment template completion rates amongst HBPC programs. To increase life-sustaining treatment template completion for Veterans receiving care from HBPC programs, the PERSIVED team applies two implementation strategies: audit with feedback and implementation facilitation. The PERSIVED team conducts semi-structured interviews, needs assessments, and process mapping with HBPC programs in order to identify barriers and facilitators to life-sustaining treatment template completion to inform tailored facilitation. Our interview data is analyzed using the Tailored Implementation in Chronic Diseases (TICD) framework, which identifies 57 determinants that might influence practice or implementation of interventions. To quickly synthesize and use baseline data to inform the tailored implementation plan, we adapted a rapid analysis process for our purposes. This paper describes a six-step process for conducting and analyzing baseline interviews through applying the TICD that can be applied and adapted by implementation scientists to rapidly inform tailoring of implementation facilitation.